2023
DOI: 10.1039/d3ra02702c
|View full text |Cite
|
Sign up to set email alerts
|

Gingerol extract-stabilized silver nanoparticles and their applications: colorimetric and machine learning-based sensing of Hg(ii) and antibacterial properties

Kittiya Plaeyao,
Ratchaneekorn Kampangta,
Yuparat Korkokklang
et al.

Abstract: Gin-AgNPs were synthesised using an eco-friendlier method that utilized AgNO3 and natural ginger solution. The application of Hg2+ sensing using Gin-AgNPs, real water samples Hg2+ sensing, machine learning analysis, and antibacterial activity assessment were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(60 reference statements)
1
2
1
Order By: Relevance
“…The optimal concentrations of the extract and AgNO3 (1 mg ginger extract in 1 mL of 1 M AgNO3 at 80 °C for 6 h) ensured sufficiently low polydispersity index of the AgNPs and pH 6 yielded the highest quantity of nanoparticles. The formation of NPs was evident by the change in color from pale yellow to dark brown, followed by additional characterization as reported earlier by Garg et al [34], Ganesan et al [35], Plaeyao et al [36], Prasad et al [37], and Mahardika et al [13], where the reaction temperature and time, and the concentration of AgNO3 are known to influence the shape and size of the ensuing NPs.…”
Section: Agnp Synthesis and Characterizationsupporting
confidence: 57%
See 1 more Smart Citation
“…The optimal concentrations of the extract and AgNO3 (1 mg ginger extract in 1 mL of 1 M AgNO3 at 80 °C for 6 h) ensured sufficiently low polydispersity index of the AgNPs and pH 6 yielded the highest quantity of nanoparticles. The formation of NPs was evident by the change in color from pale yellow to dark brown, followed by additional characterization as reported earlier by Garg et al [34], Ganesan et al [35], Plaeyao et al [36], Prasad et al [37], and Mahardika et al [13], where the reaction temperature and time, and the concentration of AgNO3 are known to influence the shape and size of the ensuing NPs.…”
Section: Agnp Synthesis and Characterizationsupporting
confidence: 57%
“…The enhanced antibacterial activity of AgNPs is due to the disruption of the bacterial membrane which was because of the synergistic effect of silver and plant antioxidants, and which can be exploited against multidrug-resistant bacteria as reported by Ganesan et al [35]. Taken together, it can be concluded that AgNPs are capable of imparting high antibacterial efficacy and can offer an advantage in broad-spectrum antibacterial and anticancer drug preparation, and also in nanomedicine, as corroborated by Plaeyao et al [36] and Swapna et al [48].…”
Section: Analysis Of Antioxidant and Antibacterial Activities Of Agnpsmentioning
confidence: 67%
“…The chromaticity parameters calculated using CIE 1931 app, obviously indicating the trends of Hg 2+ concentration-dependent color The results show that this calibration curve can be applied to determine the concentration of Hg 2+ ions in real samples. Based on the results of building the standard curve, the LOD and LOQ calculated according to formula 2 and 3 were respectively determined to be 0.048 μM and 0.16 μM, where b = 0.1911, Sy = 0.012238 with a linear range from 0.01 to 2.0 μM which was higher than those of previously published reports [2,[38][39][40]. Higher LOD were reported for Equisetum diffusum-AgNPs (0.7 μM) [2] and Vigna mungo-AgNPs (0.13 μM) [38].…”
Section: Detection Of Hg 2+ Ionscontrasting
confidence: 53%
“…While HPLC has been traditionally employed in chemical speciation analysis, often coupled with atomic absorption [ 5 ] and atomic fluorescence [ 6 , 7 ], ICP-MS has become a preferred methodology. This preference is due to its seamless integration, which allows for direct interfacing between the chromatographic output and the nebulizer inlet, and its compatibility with the flow rates of both systems, along with its superior sensitivity and selectivity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%